2019
DOI: 10.1186/s13287-019-1333-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiments to assess the effect of culture parameters on the osteogenic differentiation of human adipose stromal cells

Abstract: Background Human adipose-derived stromal cells (hASCs) have been gaining increasing popularity in regenerative medicine thanks to their multipotency, ease of collection, and efficient culture. Similarly to other stromal cells, their function is particularly sensitive to the culture conditions, including the composition of the culture medium. Given the large number of parameters that can play a role in their specification, the rapid assessment would be beneficial to allow the optimization of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Taken together, these findings suggest that the HPLG may have itself initiated the osteogenic differentiation of 2D and 3D BMSC (regardless of media supplements), thereby attenuating differences in gene expression, but promoting mineralization. Indeed, when used as a culture supplement, HPL promotes the osteogenic differentiation of MSC in vitro [ 54 – 56 ]. Moreover, several studies have reported positive effects of platelet-derived growth factors, e.g., PRP, on MSC osteogenic differentiation both in vitro and in vivo [ 23 , 57 – 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that the HPLG may have itself initiated the osteogenic differentiation of 2D and 3D BMSC (regardless of media supplements), thereby attenuating differences in gene expression, but promoting mineralization. Indeed, when used as a culture supplement, HPL promotes the osteogenic differentiation of MSC in vitro [ 54 – 56 ]. Moreover, several studies have reported positive effects of platelet-derived growth factors, e.g., PRP, on MSC osteogenic differentiation both in vitro and in vivo [ 23 , 57 – 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this issue, in particular, adipose-derived stem cells are especially suitable as they are abundant and functional with an osteogenic potential [43][44][45]. The cells used in the present experiment were extracted and characterized as described previously [30,31]. Nevertheless, as the cells were received from three different healthy donors, a heterogenous population can be assumed and cell response to electrical stimulation may differ with regard to the donor age, the location of harvesting as well as the harvesting method.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the defect to be stimulated has to be filled with bone forming stem or progenitor cells in order to restore the missing bone volume. The success of osseous regeneration largely depends on the cell type and adipose-derived stem cells are commonly studied for bone tissue engineering approaches due to their multipotency, ease of the collection and efficient culture conditions [22,30]. Therefore, the aim of our present study was to analyze and establish suitable parameters for continuous electrical stimulation in order to improve the growth, viability and proliferation of human adipose-derived stem cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Although the DoEs and optimization through MVDA for the improvement of hiPSC culture conditions [44][45][46], downstream concentration [35], and differentiation [47][48][49] have been described, examples of employing a QRM and QbD approach for the optimization of hiPSC expansion are limited, likely because ATMPs, such as hiPSCs and their derivatives, are a relatively new category in drug regulation. Indeed, ATMPs were included in the pharmaceutical legislation only in 2009 [50].…”
Section: Qbd For Hipsc Manufacturingmentioning
confidence: 99%